PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN KEMAMPUAN AWAL SISWATERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMAN 1 BONJOL - Ennike Gusti Rahmi (JURNAL PENDIDIKAN ROKANIA, 2017)
The aim of this study was to comprehend effects of jigsaw cooperative learning model and early ability on study outcomes in biology of class XI IPA students in education year 2015/2016. This quasi experiment studey used 2 x 2 factorial study design. Sampling technique used was purposive sampling, resulting in class XI IPA4 as experiment, and class XI IPA3 as control groups. The instrument employed was final test to observe students study outcome. The study results showed that there was an effect of jigsaw cooperative study model on student’s study outcome, of those with high or low early ebilities and no interaction was found between jigsaw cooperative study model with early ebility of student’s on the biology study outcome of the student’s